Citrus Consumption and Risk of Melanoma: A Dose-Response Meta-Analysis of Prospective Cohort Studies - Fang, Xuexian; Han, Dan; Yang, Jun; Li, Fulun; Sui, Xinbing (Frontiers in Nutrition, 2022)
Background: Epidemiological studies of citrus consumption in relation to melanoma risk have yielded conflicting results. This meta-analysis was performed to investigate the dose-response association between citrus consumption and risk of melanoma. Methods: Relevant prospective cohort studies were identified by searching PubMed, EMBASE, and Web of Science databases up to February 28th, 2022. Results from individual studies were pooled using a random-effects model. Results: Five prospective studies, with 8,836 melanoma cases and 977,558 participants, were included in the meta-analysis. A significantly increased risk of melanoma was associated with the highest categories of either total citrus products (RR: 1.20; 95% CI: 1.01-1.42) or citrus fruit consumption (1.15; 1.04-1.28), but consumption of citrus juice was not associated with melanoma risk (1.08; 0.97-1.21). The dose-response analyses revealed that for per 1 serving/day increase in total citrus or citrus fruit consumption, the risk of melanoma increased by 9% and 12%, respectively. An inverted U-shaped curvilinear relationship, but not linear association, was observed between citrus juice consumption and melanoma risk. Conclusions: Citrus consumption was generally associated with a greater risk of malignant melanoma. Our findings may have important public health implications with respect to preventing melanoma.